2023
DOI: 10.1111/joor.13491
|View full text |Cite
|
Sign up to set email alerts
|

Economic inequalities and temporomandibular disorders: A systematic review with meta‐analysis

Abstract: Introduction: Temporomandibular disorders (TMDs) are a common and debilitating condition that affects millions of people globally. Despite extensive research on TMDs, the exact causes of these conditions remain unclear. However, various factors, including genetics, injury and stress, have been implicated in their development. In addition to these traditional risk factors, the literature suggests that socioeconomic status (SES) may also play a role in the development and progression of TMDs. By synthesizing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 40 publications
(98 reference statements)
1
30
0
Order By: Relevance
“…In conclusion, insufficient evidence suggests that obesity is associated with an increased risk for TMDs. The mechanisms underlying this link are not fully understood, but possible explanations include mechanical stress on the TMJ and changes in hormone levels 36 . Further research is needed to understand the relationship between obesity and TMDs better and to develop effective strategies for preventing and treating these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, insufficient evidence suggests that obesity is associated with an increased risk for TMDs. The mechanisms underlying this link are not fully understood, but possible explanations include mechanical stress on the TMJ and changes in hormone levels 36 . Further research is needed to understand the relationship between obesity and TMDs better and to develop effective strategies for preventing and treating these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The candidate mediators included nine psychology-related traits (depression, feeling lonely, miserable, guilty, fed-up, nervous, worry, hurt, and tense), 19,20 four smoking and dietary behaviours (ever smoked, smoking initial, cigarettes smoked per day, alcohol intake frequency), 21 three adiposity traits (body mass index [BMI], waistto-hip ratio [WHR], body fat percentage), 22 five sleep-related traits (apnea, snoring, insomnia, daytime sleepiness, sleep duration), 23,24 one physical activity (moderate to vigorous physical activity levels), 19 two autoimmune disorders (systemic lupus erythematosus [SLE], Sjogren's syndrome [SS]), 25 insufficient Vitamin D (vitamin D supplement, serum 25-Hydroxyvitamin D levels), 25 estradiol levels in females and males, 26 lower back pain 27 and average total household income. 28 Detailed information on all GWAS included in our study is shown in Table S2.…”
Section: Data Sources For Mediatorsmentioning
confidence: 99%
“…People who have served in the military and experienced war stress are at an increased risk of developing TMD. 42 It is also important to avoid activities that may cause further strain on the TMJ, such as chewing gum, nail-biting and clenching or grinding of the teeth. 44 If the symptoms of TMD are severe or last for more than a few weeks, it is important to seek medical attention.…”
Section: Quality Assessment and Risk Of Biasmentioning
confidence: 99%